2021
DOI: 10.12669/pjms.37.2.2676
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies and outcome of lower gastrointestinal bleeding in patients presenting to a tertiary care Children’s Hospital

Abstract: Objective: To determine etiology and outcome of children with lower gastrointestinal bleeding (LGIB). Methods: This was a prospective study conducted at the Department of Pediatric Gastroenterology and Hepatology, Children’s Hospital and The Institute of Child’s Heath, Multan, Pakistan, from July 2019 to March 2020. A total of 148 cases presented with bleeding per rectum and underwent colonoscopy, were included. Children of both genders and aged three month to 15 years were included. Detailed history, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(34 reference statements)
2
2
0
1
Order By: Relevance
“…Based on the clinical examination, pallor was observed amongst 115 (46%) patients, weight loss in 52 (20.8%) patients and tachycardia was observed in 45 (18%) patients while hypotension was observed in 38 (15.2%) in the current study. Other previous studies reported similar observations 14,16,17 . Juvenile colonic or rectal polyps were the most frequent finding in the present investigation, occurring in 36.4 per cent of cases.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Based on the clinical examination, pallor was observed amongst 115 (46%) patients, weight loss in 52 (20.8%) patients and tachycardia was observed in 45 (18%) patients while hypotension was observed in 38 (15.2%) in the current study. Other previous studies reported similar observations 14,16,17 . Juvenile colonic or rectal polyps were the most frequent finding in the present investigation, occurring in 36.4 per cent of cases.…”
Section: Discussionsupporting
confidence: 82%
“…Another study done in India reported high male to female ratio (2.16:1) amongst children with LGIB undergoing colonoscopy17 . Another study also reported comparable findings14 . The mean age was 6.80 (± 1.50) years in our study.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Phân bố giới tính trong nghiên cứu của chúng tôi tương tự với các nghiên cứu trong nước và trên thế giới. XHTH dưới có xu hướng gặp ở trẻ trai nhiều hơn trẻ gái, tỷ lệ trẻ trai/trẻ gái trong nghiên cứu của Lê Quang Quỳnh là 2,1/1 3 và Muhammad Abu Talib (2021) là 1,3/1 4 . Tuổi trung bình là 5,5 ± 4,6 tuổi (Bảng 1).…”
Section: Bàn Luậnunclassified